Oral Co-Supplementation of Curcumin, Quercetin, and Vitamin D3 as an Adjuvant Therapy for Mild to Moderate Symptoms of COVID-19—Results From a Pilot Open-Label, Randomized Controlled Trial - Khan, Amjad; Iqtadar, Somia; Mumtaz, Sami Ullah; Heinrich, Michael; Pascual-Figal, Domingo A.; Livingstone, Shona; Abaidullah, Sajid (Frontiers in Pharmacology, 2022)
Background: Curcumin, quercetin, and vitamin D3, the common elements of human food, exhibit promising anti-inflammatory, immunomodulatory, antiviral and antioxidant pharmacological effects. Objective: The present study aimed to investigate the potential therapeutic benefits of oral co-supplementation of curcumin, quercetin, and vitamin D3 as adjuvant therapy for early-stage of symptomatic COVID-19 infection in a pilot open label, randomized, controlled trial conducted at King Edward Medical University teaching hospital, Lahore, Pakistan. Methods: 50 RT-PCR confirmed, mild to moderate symptomatic COVID-19 outpatients were randomized to receive the standard of care (SOC) (n=25) (control arm) or to a daily oral co-supplementation of 168 mg curcumin, 260 mg quercetin and 360 IU of vitamin D3 (cholecalciferol), combinedly referred as CQC as add-on to SOC (n=25) (CQC arm) for 14-days. The SOC include paracetamol with or without antibiotic (azithromycin). SARS-CoV-2 RT-PCR test, COVID-19 associated acute symptoms and biochemistry including C-reactive protein (CRP), D-dimer, lactate dehydrogenase (LDH), ferritin, and complete blood count (CBC) were evaluated at baseline and follow-up day 7. Results: Patients who received the CQC adjuvant therapy were expeditiously tested negative for SARS-CoV-2 i.e. 15 (60.0%) vs 5 (20.0%) of the control arm, p=0.009. COVID-19 associated acute symptoms were rapidly resolved in the CQC arm i.e. 15 (60.0%) vs 10 (40.0%) of the control arm, p=0.154. Patients in the CQC arm experienced a greater fall in serum CRP levels i.e (median (IQR) 34.0 (21.0, 45.0) to 11.0 (5.0, 16.0) mg/dl as compared to the control arm i.e. 36.0 (28.0, 47.0) to 22.0 (15.0, 25.0) mg/dl, p=0.006. The adjuvant therapy of co-supplementation of curcumin, quercetin and vitamin D3 was well-tolerated by all 25 patients and no treatment-emergent effects, complications, side-effects, or serious adverse events were reported. Conclusions: The co-supplementation of curcumin, quercetin and vitamin D3 may possibly have a therapeutic role in the early stage of COVID-19 infection including speedy negativity of SARS-CoV-2, resolution of acute symptoms and controlling of hyperinflammatory response. In combination with routine care, the adjuvant co-supplementation of curcumin, quercetin and vitamin D3 may possibly help in the speedy recovery from early mild to moderate symptoms of COVID-19. Further research is warranted.